Ken Hirschkop’s “new Bakhtin” for the English-speaking students - Oleg Osovsky; Svetlana Dubrovskaya; Vera Kirzhaeva; Elizaveta Maslova (Dialogic Pedagogy, 2022)
A review of Hirschkop K. The Cambridge Introduction to Mikhail Bakhtin. Cambridge: Cambridge University Press, 2021.  xvi, 250 p. (Cambridge Introductions to Literature).